Bugs - York, Penelope (London ; New York : DK, 2002)
Describes a variety of insects and their behavior, discussing metamorphosis, camouflage, defenses, and their benefits to people.
"Open your eyes to a world of discovery"--Cover.
Includes index.
Accelerated Reader AR
Keywords: Insects -- Juvenile literature